Determinants of Financial Literacy and Investment Behavior: Evidence from University Students - Muhammad Sulaman Akram; Noureen A. Khan; Baharom Hamid; Mudeer Khattak (NUML International Journal of Business & Management)
The research explores Financial Literacy (FL) among undergraduate students. The study aims to evaluate the FL of a specific group of undergraduate students. It investigates how different demographic and socioeconomic factors influence these students' FL and analyzes various demographic and socioeconomic factors to determine if they are better predictors of FL among students. The demographic and socioeconomic factors analysis shows that FL among university students is generally low. Male students studying business and coming from higher-income families have improved FL, while students in their early twenties typically have lower levels of FL. Educators should help low-income parents and women with FL, promoting financial inclusion. Helping women improve their financial understanding brings numerous benefits and positively influences the financial attitudes of their children, encouraging them to foster strong financial skills and knowledge from an early ages.